(untitled) (Alternate Horizons, 2021)
The African youth population is expected to increase up to over 830 million by 2050 and an estimated 263 million young people may not be gainfully employed by 2025 according to the African Development Bank projection. This is quite worrisome as there is currently an increase in migration of young and skilled Africans to other continents, as well as poor living conditions, increased crime rates, and social vices among the African youth population as a result of unemployment, amongst other factors. Urgent attention is, therefore, required towards reducing the rate of unemployment in Africa. Although job creation and the provision of economic opportunities for citizens are constitutional duties of government officials and public office holders, the alarming increase in youth unemployment calls for a more holistic and sustainable approach to addressing this challenge – hence the need for human capacity building towards self-employment and sustenance. The promotion of entrepreneurship through formal and informal education in Africa, provision of mentorship programmes, and start-up funds will provide a short- and long-term solution to the scourge of youth unemployment in Africa.